Current Challenges in Visibility Improvement in Sichuan Basin - Gang Zhao; Min Hu; Zirui Zhang; Lizi Tang; Dongjie Shang; Jie Ren; Xiangxinyue Meng; Yuan Zhang; Miao Feng; Yina Luo; Shishi Yang; Qinwen Tan; et al. (Geophysical Research Letters)
Abstract The visibility in the Sichuan Basin (SB) was worse than that in the North China Plain (NCP) for the same level of PM2.5. One well‐known reason is that the aerosol extinction enhancement due to hygroscopic growth in the SB was stronger than that in the NCP because the relative humidity (RH) in the SB was higher than that in the NCP. However, the visibility was worse in the SB under the same PM2.5 and RH levels. The volume extinction efficiency (VEE) is kept between 7 and 8 for different PM2.5 in the SB, while the VEE increased from 4.6 to 7.2 when the PM2.5 level increased from 20 to 180 μg/m3 in the NCP. The difference in VEE resulted from the different particle number size distributions. Our research demonstrates that the VEE is an important factor that influences visibility and provides new insight into visibility impairment for the SB.